Review of the state-of-the-art in patent information and forthcoming evolutions in intelligent patent informatics - Bonino, Dario; Ciaramella, Alberto; Corno, Fulvio (World patent information, 2010)
Information and meta-information related to national and international patents is a critical asset for every innovative company. The complexity of managing, searching, analyzing and relating such information to the needs of the company, in the different user tasks, is tackled by innovative knowledge management solutions, that aim at supporting the users in such daunting tasks. This paper aims at presenting a comprehensive and updated overview of patent information and of innovative solutions in patent informatics, in particular concerning intelligent and semantic solutions proposed in recent years. The analysis starts from the actual requirements of different types of users of patent information, and the typical information management tasks they require. Innovations, covering all the layers from data bases to algorithms to on-line services, are also critically presented and compared, and current research trends are outlined.